2021
DOI: 10.15562/bmj.v10i1.2181
|View full text |Cite
|
Sign up to set email alerts
|

Use of smartphone-based self-monitoring blood glucose application in type 2 diabetes mellitus patients in Indonesia: A pre and post-test study

Abstract: Background: The utilization of technology in diabetes management, especially self-monitoring blood glucose (SMBG), is growing rapidly. However, the effectiveness of SMBG applications on the smartphone is not yet known. This study aims to assess the effectiveness of using a smartphone-based SMBG application in type 2 diabetes mellitus (T2DM) patients in the Indonesian population.Methods: This is a quasi-experimental (before and after) study conducted at three tertiary hospitals in Jakarta and Malang, Indonesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, leveraging technology such as the use of smartphone-based SMBG could be an option. 23 Also, given the modest reliability of the current measure of the predictive factors, the question items could be revised and modified with consideration for further exploratory factor analyses and for streamlining the scales. In addition, as the present study was a cross-sectional study and adopted convenient sampling, it is suggested that random sampling and a longitudinal method could be used to enhance the empirical design of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, leveraging technology such as the use of smartphone-based SMBG could be an option. 23 Also, given the modest reliability of the current measure of the predictive factors, the question items could be revised and modified with consideration for further exploratory factor analyses and for streamlining the scales. In addition, as the present study was a cross-sectional study and adopted convenient sampling, it is suggested that random sampling and a longitudinal method could be used to enhance the empirical design of the study.…”
Section: Limitationsmentioning
confidence: 99%